Post-COVID rhinocerebral mucormycosis: an otolaryngologists nightmare - Joshi, Samir V.; Dubey, Nimita; Havaldar, Rajesh R.; Wakhlu, Amish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Rhinocerebral mucormycosis which was considered to be a rare occurrence in the pre-COVID era is currently emerging as a life-threatening disease with seemingly poor prognosis in post COVID recovered patients. Prompt diagnosis with urgent surgical and medical management is vital to a positive outcome. Methods: A retrospective observational study and analysis was done among patients of biopsy proven mucormycosis with preceding history of COVID 19 disease between March 2021 to April 2021 in a tertiary care state run hospital at Pune coinciding with the sudden surge and second COVID 19 wave. Results: 20 0ut of 23 patients were having a history of type 2 diabetes mellitus for a mean duration of 4±3.5 years. The most common presenting complaint was unilateral facial swelling, periorbital pain, swelling and oedema in 18 out of 23 patients. All patients had COVID infection within the last one month of presentation with mean duration of 18±8.4 days. Out of 23 patients 16 survived while 19 patients had permanent vision loss and ophthalmoplegia. Conclusions: Establishing the possibility of invasive secondary fungal infections in patients with history of COVID-19 infection especially in patients with pre-existing risk factors should raise high index of suspicion. Prompt early diagnosis and treatment should be started to reduce morbidity and mortality.